Comparison of Transcutaneous and Arterial Blood Gas Analyses in Patients with Sepsis and Septic Shock - Reşit Saruhan; Berna Kaya Uğur; Süleyman Ganidağlı; Pınar Tümtürk (Galenos Yayinevi, 2021)
Objective:This study aims to compare the effectiveness of non-invasive pressure of transcutaneous CO2 (PtcCO2) and O2 (PtcO2) analyzers versus conventional blood gas sampling in patients with sepsis and septic shock.Materials and Methods:Sepsis patients without a need for inotrope support (sepsis) were prospectively enrolled to group 1 (n=50), whereas group 2 (n=50) was composed of patients needing inotropes (septic shock). Demographic data, laboratory tests, Acute Physiology and Chronic Health Evaluation-II (APACHE-II) and Sequential Organ Failure Assessment (SOFA) scores, standard monitoring data, data of blood gas analysis (pH, PaCO2, PaO2, and SaO2), and transcutaneous CO2 and O2 were collected at the first, second, third, and fourth hours.Results:No significant difference was noted between the groups in terms of demographic parameters, baseline white blood cell, hematocrit, baseline heart rate, central venous pressure, respiratory rate, and positive end-expiratory pressure values. Group 2 had significantly higher serum urea and creatinine levels and lower albumin levels and mean arterial pressure, whereas group 1 had significantly lower APACHE-II and SOFA scores and peak inspiratory pressure and FiO2. No significant difference was noted between the PtcCO2 and PaCO2 values in group 1, whereas the PtcCO2 values of group 2 were significantly lower than PaCO2. PtcO2 and PaO2 values were significantly lower in group 1, whereas PtcO2 vs PaO2 values were significantly lower in group 2. A strong correlation was noted between arterial and transcutaneous CO2 and O2 values in both the groups.Conclusion:PtcCO2 assessment may be an alternative method in patients with sepsis but not in septic shock. PtcO2 measurement may not be a reliable method for patients with sepsis and septic shock.